1979
DOI: 10.1111/j.1365-2761.1979.tb00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral dysplasia in young fish exposed to the herbicide trifluralin

Abstract: Sheepshead minnows, Cyprinodon variegatus Laeepede, exposed to 5 5 to 31 /xg/1 of the herbicide trifluralin, throughout their first 28 days of life, developed a heretofore undescribed vertebral dysplasia. This dysplasia consisted of semisymmetrical hypertrophy of vertebrae (three to 20 times normal), characterized by foci of osteoblast and fibroblasts actively laying down bone and bone precursors. Effects of the abnormal vertebral development were dorsal vertebral growth into the neural canal, ventral compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…Those that did hatch had tail deformities. Similar tail malformations have been observed in Sheephead minnow {Cyprinodon variegates , Cyprinodontidae) after exposure to herbicide trifuralin (Couch et al 1979);, in Japanese carp (Puntius gonionotus, Bleeker) after exposure to hydrogen sulfide (H 2 S )…”
Section: Discussionsupporting
confidence: 60%
“…Those that did hatch had tail deformities. Similar tail malformations have been observed in Sheephead minnow {Cyprinodon variegates , Cyprinodontidae) after exposure to herbicide trifuralin (Couch et al 1979);, in Japanese carp (Puntius gonionotus, Bleeker) after exposure to hydrogen sulfide (H 2 S )…”
Section: Discussionsupporting
confidence: 60%
“…The presence of inflammatory cells is the fourth change to be described, and this is apparently the first description of these cells, as they are not mentioned in previous histologic examinations of short columns (Vavra 1906, Schaferna 1923, Henschke et al 1982, Hansen & Yalew 1988, Lom et al 1991 or columns with similar changes (Couch et al 1979). RubensDuval & Desse (1972), who also found protrusion of chordal tissue into the vertebral canal, state that no inflammatory lesions were found.…”
Section: Discussionmentioning
confidence: 76%
“…The pathology associated with the parasite is, especially during the early stages, reminiscent of fish exposed to pesticides as described by Couch et al (1979) and Middaugh et al (1990). Couch et al (1979) suggested a number of mechanisms by which herbicides may directly or indirectly influence vertebral dysplasia in fish including influencing or stimulating osteogenic tissues and cells or the hormonal control of calcium utilisation and compartmentalisation in the fish host. It is interesting to speculate on whether M. buckei has a similar mechanism in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Most skeletal deformities occur during embryogenesis or early in the life of the fish. A number of factors can lead to these abnormalities including exposure to pesticides including organochlorides and organophosphates (Couch et al 1979, Middaugh et al 1990), heavy metals (Roberts 1989), inappropriate temperature or movement during critical phases of embryogenesis (Brown and Núñez 1998) and disease. Arguably, one of the most studied diseases causing skeletal deformities in fish is whirling disease caused by the myxozoan Myxobolus cerebralis Hofer, 1903.…”
mentioning
confidence: 99%